Moderate Intensity Training By Listening To Music Decreases Interleukin-6 Levels In Rats - Septyaningrum Putri Purwoto; Adi Pranoto; Hartono Hartono; Sugiharto Sugiharto (Universitas STRADA Indonesia, 2020)
The design of this study is the randomized control group posttest-only design, 21 of Rattus Norvegicus Strain Wistar male, 20-24 weeks, 250 ± 350 grams and randomly divided into 3 groups namely CONT (n = 7, control without treatment), MIT (n = 7, moderate intensity training, treadmill with speed 14-16 m/min for 15-30 minutes listening to music tempo 160 beats/min) and HIT (n = 7, high intensity training, treadmill with speed 22-25 m/min for 15-30 minutes listening to music tempo 160 beats/min). The intervention was started from 17.00-20.00 WIB with a frequency of 3 times / week for 10 weeks. Blood is drawn for 12 hours after the last training. Measurement of IL-6 serum levels using the ELISA method. Data analysis techniques using ANOVA test and LSD post hoc test with the Statistical Package for Social Science (SPSS).